2019
DOI: 10.4314/rjmhs.v2i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease (CKD): knowledge of risk factors and preventive practices of CKD among students at a University in Rwanda

Abstract: BackgroundChronic Kidney Disease (CKD) is a global public health burden. Most people miss the early subtle signs that can develop at any age. CKD has severe complications, including End-stage Renal Disease. ObjectiveTo assess the knowledge level of CKD risk factors and preventive practices among university students in Rwanda. Methods A cross-sectional study design was used from April to May 2017. A stratified random sampling technique was used to recruit 260 university students. A 36-item questionnaire was sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
(32 reference statements)
1
8
1
Order By: Relevance
“…We noticed that 29.2% of the sample with good knowledge were students. These findings are similar to the results of a cross-sectional study conducted in Rwanda and which found a little more than one half of university students surveyed had a strong understanding of kidney illness [ 31 ]. A telephonic study conducted in Hong Kong revealed respondents had a high degree of knowledge, with the majority aware of renal function and dietary sodium as risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…We noticed that 29.2% of the sample with good knowledge were students. These findings are similar to the results of a cross-sectional study conducted in Rwanda and which found a little more than one half of university students surveyed had a strong understanding of kidney illness [ 31 ]. A telephonic study conducted in Hong Kong revealed respondents had a high degree of knowledge, with the majority aware of renal function and dietary sodium as risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…In comparison to the undergraduate students' knowledge on CKD, two studies performed in Rwanda revealed a similar pattern (17,18), whereby the knowledge of the disease and its preventive measures among students in Rwanda were considered low. Somehow, these results contradict a previous study among final year nursing students in Nigeria (12) that found an overall good knowledge on CKD, especially on the anatomical structure functions, along with the signs and symptoms of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…It's also possible for a student or a group of a certain age-set to copy the lifestyles of other students or groups including those lifestyles that can put one at the risk of contracting or developing chronic diseases. Even Ngendahayo et al [34] have found an average age of university students that is above the range of 17-24 years, in which case they have sampled students whose average age is 29 years. The fact that the university environment is more or less the same as that of general community: in terms of moving in and out of campus circumferences at all times, ethnic composition, a larger percentage residing offcampus with the general public, relationships and interactions that are both unrestricted and without boundaries in terms of age, social class, believes and so on, the university students' group cannot be thought to be special that is excluded and isolated from the general public's influence and challenges.…”
Section: The Diseases Among the University Studentsmentioning
confidence: 99%
“…Ngendahayo et al [34] carried out research on university students (University of Technology and Arts of Byumba, Rwanda) to evaluate their knowledge on chronic kidney disease (CKD) and the preventive measures adopted. A questionnaire was used as the main data collecting tool while the sample was randomly selected based on a stratified random sampling method.…”
Section: Literature On Chronic Diseases Among University Studentsmentioning
confidence: 99%